The ‘Sogdian Deities’ Twenty Years on: A Reconsideration of a Small Painting from Dunhuang - Russell-Smith, Lilla (Dynamics in the history of religions, 2022)
In this article I reconsider the reasons why the so-called ‘Sogdian deities’ became so well-known in Dunhuang (敦煌) studies, Zoroastrian studies and Silk Road studies and present new evidence that supports my original view that a small painting on paper, P. 4518 (24), was made for a specifically Uyghur donor in Dunhuang, who was most probably Buddhist. It may also show Manichaean features, as Uyghur Buddhist art in the early period frequently did. Finally, I consider the possibility that the female deity on the right may have an astral meaning and is seated on a dog symbolising Sirius the dog star.